Islamic Criminal Subtance in the RUU- KUHP ( Review of legal politics of RUU-KUHP) - Anshori Anshori (Syiah Kuala Law Journal, 2023)
Islamic law, especially jinayah (Islamic criminal law) is a legal system, which cannot be ignored in a country where the majority of the population is Muslim. Enacting the law for adherents of a religion is basically a form of religious adherence to their religion. For this reason, the prohibition of a religion in carrying out its teachings, including part of a constitutional violation, which is technically protected. As a former Dutch colony, the colonial legal system is the most colorful in the country's system. Thus, the existing legal system is often marginalized as a legal system in the country. The formulation of the problem in this research is why Islamic criminal law has not become a legal system in Muslim-majority countries, and whether the substance of Islamic criminal law is absorbed in the draft criminal law code.In this study using juridical empirime as a methodology, using a  approach to the concept of legal politics and historis process of legislation. The conclusion in this study, that the substance of Islamic criminal law has not become the dominant color as a legal system in a Muslim-majority country, this is due to the lack of strong legal politics that fights for the substance of Islamic criminal law to give its war against the criminal law that will be enforced.